2017
DOI: 10.5935/0946-5448.20170005
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Results of Intra Tympanic Gentamicin and Dexamethasone on Hearing and Tinnitus in Meniere’s disease: A Case Control Study

Abstract: Objective: The role of this study was to evaluate the effectiveness of intra tympanic administration of Gentamicin(40 mgs/ml) and Dexamethasone 0.5 ml(4 mgs/ml) on hearing and tinnitus of patients who had recurrent acute attacks of vertigo, tinnitus and hearing loss. Study Design: 60 consecutive patients of Meniere's disease were randomly divided into 3 groups of twenty patients each. Group A included 20 patients who received intra tympanic gentamicin, Group B included 20 patients who received intra tympanic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, IT injections deliver significantly smaller amounts of drug to the inner ear due to minimal diffusion through the RWM and drainage of the drugs out of the ear via the Eustachian tube. [ 12 ] Additionally, the pharmacokinetic profile of the drugs administered intratympanically to the inner ear are highly dependent on the physiochemical property of the drug itself. [ 37 ] Drug delivery materials were subsequently developed which were placed on or near the RWM, yet when these materials are displaced, the drug delivery is compromised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, IT injections deliver significantly smaller amounts of drug to the inner ear due to minimal diffusion through the RWM and drainage of the drugs out of the ear via the Eustachian tube. [ 12 ] Additionally, the pharmacokinetic profile of the drugs administered intratympanically to the inner ear are highly dependent on the physiochemical property of the drug itself. [ 37 ] Drug delivery materials were subsequently developed which were placed on or near the RWM, yet when these materials are displaced, the drug delivery is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…[9] To address these issues, studies have repeatedly shown that dexamethasone (DXM), a corticosteroid, combats HC death by altering the expression levels of apoptosis related genes. [10][11][12][13][14][15] While systemic forms of drug delivery of DXM are available, undesirable side effects are common and the effective dose may not reach the ear when given systemically. [16] Other currently available treatment methodologies and strategies, apart from new drug development, include intratympanic (IT) injections of drugs, cochlear implants, stem cell therapies, manipulation of gene expression, viral vectors, thermosensitive gels, nanoparticles, and placement of drug delivery materials on the surface of the round window membrane (RWM), amongst others.…”
Section: Introductionmentioning
confidence: 99%